Development and application of a three-dimensional GPGPU-parallelized FDEM for modelling rock fragmentation by blast. Issue 3 (October 2021) - Liu, Hongyuan; Fukuda, Daisuke; Han, Haoyu
Abstract: Numerical modelling of rock fragmentation by blast is an important step to the optimum fragmentation. Combined finite-discrete element method (FDEM) has recently been proven to be one of the most promising methods for modelling the fracture and fragmentation of rocks under various loading conditions including rock blasting. However, almost all FDEM modellings of rock blasts are conducted in two-dimension. Correspondingly, this study implements a three-dimensional (3D) hybrid finite-discrete element method (HFDEM) parallelized on the basis of the general-purpose graphic-processing-unit (GPGPU) to model the fracture and fragmentation process of rock by blast. The main components of HFDEM3D include robust fracturing algorithm, efficient contact activation approach and various implementations of gas and rock interactions, which are firstly briefly reviewed here and introduced in detail in authors' various former publications. The GPGPU-parallelized HFDEM3D is then applied to model the rock fracture and fragmentation process by the detonation of a single borehole and simultaneous and consecutive detonations of multiple boreholes.